2015
DOI: 10.1249/mss.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Temperature of Ingested Water during Exercise Does Not Affect Body Heat Storage

Abstract: We show that ingestion of hot water elicits a greater HL relative to cold water ingestion during exercise. However, this response was only compensated for the heat of the ingested fluid as evidenced by similar ΔHb between conditions. Therefore, our findings indicate that relative to cold water ingestion, consuming hot water does not provide a thermoregulatory advantage. Both hot and cold water ingestion results in the same amount of heat stored during prolonged moderate-intensity exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A study from our research group (1) subsequently demonstrated using partitional calorimetry that the lower sweat production with the ingestion of cold (1.5-C) and cool (10-C) fluid relative to a thermoneutral fluid (37-C) leads to a reduction in estimated skin surface evaporative heat loss that is approximately equal to the greater internal heat exchange with the ingested cold fluid, thereby resulting in similar net heat loss and therefore similar changes in body heat storage irrespective of fluid temperature. This finding has been recently corroborated using direct measurements of evaporative heat loss via direct calorimetry (19).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…A study from our research group (1) subsequently demonstrated using partitional calorimetry that the lower sweat production with the ingestion of cold (1.5-C) and cool (10-C) fluid relative to a thermoneutral fluid (37-C) leads to a reduction in estimated skin surface evaporative heat loss that is approximately equal to the greater internal heat exchange with the ingested cold fluid, thereby resulting in similar net heat loss and therefore similar changes in body heat storage irrespective of fluid temperature. This finding has been recently corroborated using direct measurements of evaporative heat loss via direct calorimetry (19).…”
mentioning
confidence: 59%
“…In the present study, ICE ingestion during exercise, relative to 37-C fluid ingestion, led to a disproportionately greater reduction in E sk compared to the difference in H fluid with ICE ingestion. In a recent publication investigating the effect of warm (50-C) and cold (1.5-C) water ingestion on heat balance during exercise using direct calorimetry (19), the authors observed no difference in body heat storage between trials indicating proportional changes in E sk with different levels of H fluid . Using the partitional calorimetry method, we previously observed a similar finding with 1.5-C, 10-C, and 37-C fluid ingestion (1).…”
Section: Discussionmentioning
confidence: 99%
“…; Lamarche et al . )), these conditions provided all individuals with respective net heat loads of approximately 400, 500 and 600 W. The first and lowest heat load used was selected to be greater than the net heat load used in previous research (∼340 W; Jay et al . ; Cramer & Jay, ).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve our objective, we used an exercise model consisting of three successive bouts of semi-recumbent cycling performed at progressively greater fixed rates of metabolic heat production (and therefore heat load) in hot, dry conditions (40°C, 12% relative humidity). After accounting for the additional dry heat gain from the environment to the skin (estimated from our previous work to be ß100 W (Gagnon et al 2013;Lamarche et al 2015)), these conditions provided all individuals with respective net heat loads of approximately 400, 500 and 600 W. The first and lowest heat load used was selected to be greater than the net heat load used in previous research (ß340 W; Jay et al 2011;Cramer & Jay, 2015). We hypothesized that fitness-related differences in whole-body evaporative heat loss are heat-load dependent and that the magnitude of those differences would be greater with progressive increases in net heat load.…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the interest of Bain et al (2) in our work (6). Recently, Bain et al (1) argued that the reported reductions in body heat storage with cold water ingestion (7,8) were likely due to the inherent underestimation of body heat storage associated with thermometry (5).…”
Section: R E S P O N S Ementioning
confidence: 87%